2018
DOI: 10.1103/physreve.98.052203
|View full text |Cite
|
Sign up to set email alerts
|

Ring modes supported by concentrated cubic nonlinearity

Abstract: We consider the one-dimensional Schrödinger equation on a ring, with the cubic term, of either self-attractive or repulsive sign, confined to a narrow segment. This setting can be realized in optics and Bose-Einstein condensates. For the nonlinearity coefficient represented by the delta-function, all stationary states are obtained in an exact analytical form. The states with positive chemical potentials are found in alternating bands for the cases of the self-repulsion and attraction, while solutions with nega… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Current dynamics have been studied through either a rotational drive [21], through the interaction between symmetry breaking potentials and rotation such as in lattice rings [22][23][24], or through rotating defects [25][26][27]. Solutions of the Gross-Pitevskii equation (GPE) for a 1D ring, in the free case and with various sets of potentials, have been established by analyzing its spectrum either numerically and/or through the use of Jacobi elliptic functions [28][29][30][31][32][33][34]. The spectrum for a moving link and repulsive interactions was analyzed thoroughly in [35].…”
Section: Introductionmentioning
confidence: 99%
“…Current dynamics have been studied through either a rotational drive [21], through the interaction between symmetry breaking potentials and rotation such as in lattice rings [22][23][24], or through rotating defects [25][26][27]. Solutions of the Gross-Pitevskii equation (GPE) for a 1D ring, in the free case and with various sets of potentials, have been established by analyzing its spectrum either numerically and/or through the use of Jacobi elliptic functions [28][29][30][31][32][33][34]. The spectrum for a moving link and repulsive interactions was analyzed thoroughly in [35].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the parameters, the barrier can resonantly couple the +1 and -1 states (light gray arrow) or induce an adiabatic transition between the +1 and 0 states (dashed blue arrow).force [27]. For sufficiently small obstacles stationary circulating states may exist [28][29][30], while a forced flow past a larger obstacle results in soliton emission [31][32][33].Most of the previous studies were performed in a rotating frame, thus imposing a flow onto the ring, allowing to estimate the nucleation rate of phase-slips [34]. For intermediate to strong interactions and small barriers it has been shown that the decay of persistent currents is related to the low-energy excitations in the ring [35].In this work, we investigate how a free current flows in 1D: as illustrated in Fig.…”
mentioning
confidence: 99%
“…For a microscopic impurity the decay rate has been estimated by computing the drag force [27]. For sufficiently small obstacles stationary circulating states may exist [28][29][30], while a forced flow past a larger obstacle results in soliton emission [31][32][33].…”
mentioning
confidence: 99%